Simulation of the Influence of Wind Speed on the Power Output of a Vertical Axis Wind Turbine - Novan Habiburrahman Habiburahman; Novie Ary Priyanti; M. Zainul Muttaqin; Ari sam Primadiarta; Agung Hariadi (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2025)
This study aims to analyze the effect of varying wind speeds on the power output generated by a Vertical Axis Wind Turbine (VAWT). This type of turbine holds great potential for harnessing wind energy in both urban and rural areas, particularly due to its ability to operate under fluctuating wind directions. The methodology employed is numerical simulation based on Computational Fluid Dynamics (CFD), which models fluid flow around the turbine rotor at wind speeds ranging from 2 m/s to 12 m/s. Key parameters analyzed include power coefficient (Cp), torque, and mechanical power output. The simulation results indicate a nonlinear relationship between wind speed and power output, where increasing wind speed significantly enhances power up to a certain optimum point, beyond which turbulence and energy losses become more dominant. These findings provide a foundation for optimizing VAWT design and selecting suitable installation sites according to local wind conditions. This research also supports the development of sustainable and environmentally friendly renewable energy technologies, particularly for small- to medium-scale applications.